Next generation sequencing approaches to evaluate water and wastewater quality. (15th April 2021) - Garner, Emily; Davis, Benjamin C.; Milligan, Erin; Blair, Matthew Forrest; Keenum, Ishi; Maile-Moskowitz, Ayella; Pan, Jin; Gnegy, Mariah; Liguori, Krista; Gupta, Suraj; Prussin, Aaron J.; Marr, Linsey C.; et al.
Highlights: Next generation sequencing (NGS) is increasingly used to study water/wastewater. NGS can provide insight into the composition of complex microbial communities. Key trends in NGS methodologies in water/wastewater are summarized. Common applications of NGS to address challenges in water/wastewater are identified. Barriers to application of NGS, and means to overcome them, are discussed. Abstract: The emergence of next generation sequencing (NGS) is revolutionizing the potential to address complex microbiological challenges in the water industry. NGS technologies can provide holistic insight into microbial communities and their functional capacities in water and wastewater systems, thus eliminating the need to develop a new assay for each target organism or gene. However, several barriers have hampered wide-scale adoption of NGS by the water industry, including cost, need for specialized expertise and equipment, challenges with data analysis and interpretation, lack of standardized methods, and the rapid pace of development of new technologies. In this critical review, we provide an overview of the current state of the science of NGS technologies as they apply to water, wastewater, and recycled water. In addition, a systematic literature review was conducted in which we identified over 600 peer-reviewed journal articles on this topic and summarized their contributions to six key areas relevant to the water and wastewater fields: taxonomic classification and pathogen detection, functional and catabolic gene characterization, antimicrobial resistance (AMR) profiling, bacterial toxicity characterization, Cyanobacteria and harmful algal bloom identification, and virus characterization. For each application, we have presented key trends, noteworthy advancements, and proposed future directions. Finally, key needs to advance NGS technologies for broader application in water and wastewater fields are assessed. Graphical abstract: Image, graphical abstract